Phytochemistry : Volume 2: Pharmacognosy, Nanomedicine, and Contemporary Issues - Egbuna, Chukwuebuka; Kumar, Shashank; Chinenye Ifemeje, Jonathan; Vikas Kurhekar, Jaya; Apple Academic Press (Toronto ; New Jersey : Apple Academic Press, 2018)
As volume 2 of this three-volume set on phytochemistry, this book features chapters that comprehensively review a selection of important recent advances in ethnopharmacology and alternative and complementary medicines. It also presents many informative chapters on the medicinal potential of phytochemicals in the treatment and management of various diseases, such as cancer, diabetes, diabetic nephropathy, autoimmune diseases, neurological disorders, male infertility, and more.
Part 1: Ethnomedicine And Pharmacognosy -- 1. Pharmacognosy and Prehistoric Uses of Medicinal Plants -- Chukwuebuka Egbuna, Nadia Sharif, and N. Shaista Jabeen -- 2. Complementary and Alternative Systems of Medicines -- Vinesh Kumar and Yogita Sharma -- 3. Ethnobotanical Study of Indigenous Peoples Medicinal Plants -- Felix Ifeanyi Nwafor and Stella I. Inya-Agha -- 4. Herbal Medicine: A Case Study of Nigerian Medicinal Plants -- A. Oyedepo, Temitope -- 5. Plant Species Utilized for Ethnoveterinary Practices in India -- V. Lakshminarayana and G. M. Narasimha Rao -- 6. Antioxidants and Phytochemicals -- Chukwuebuka Egbuna -- 7. Roles of Phytochemicals in the Prevention and Treatment of Various Diseases -- Intan Soraya Che Sulaiman, Shibani Sukhi, and Azham Mohamad -- 8. Phytochemicals as Oxidative Stress Mitigators -- Ashutosh Gupta and Abhay K. Pandey -- 9. Antimicrobial Medicinal Plants as Effective Natural Bioresources -- Jaya Vikas Kurhekar -- 10. Medicinal Plants with Anti-Venom Activities -- Habibu Tijjani and Chukwuebuka Egbuna -- 11. Medicinal Potentials of Green Tea -- Frederick O. Ujah -- 12. Antioxidant Potentials of Cinnamon -- S. Zafar Haider et al. -- 13. Phytochemical as the Hope for the Treatment of Hepatic and Neuronal Disorders -- Swagata Das et al. -- 14. Role of Phytochemicals in the Treatment of Male Infertility -- Vijaykumar K. Parmar and Ketan Variya -- 15. Roles of Medicinal Plants in the Treatment of Cancer -- Prabhat Upadhyay et al. -- 16. Methylated Flavonoids as a Novel Inhibitor of Metastasis in the Cancer Cell -- Prem Prakash Kushwaha, Pushpendra Singh, and Shashank Kumar -- 17. Medicinal Roles of Phytomolecules in the Treatment and Management of Diabetes Mellitus -- Maria Aslam, Sidra Khalid, and Hafsa Kamran -- 18. Roles of Phytomolecules in the Treatment of Diabetic Nephropathy -- Rashmi Shukla, Prabhat Upadhyay, and Yamini B. Tripathi -- 19. Phytochemicals as Protagonist for the Treatment and Management of Autoimmune Diseases -- Pragya Mishra, Parjanya Kumar Shukla, and Raghvendra Raman Mishra -- Part 3: Nanoparticle Biosynthesis And Its Biomedical Applications -- 20. Green Biosynthesis of Metallic Nanoparticles -- Seshu Vardhan Pothabathula, Prem Prakash Kushwaha, and Shashank Kumar -- 21. Cytotoxicity and Biomedical Applications of Metal Oxide Nanoparticles Synthesized from Plants -- Hii Yiik Siang et al. -- 22. Biosynthesis of Carbon Dots Nanoparticles from Plants -- Hameed Shah and Ashfaq Ahmad Khan -- Part 4: Phytochemicals As Friends And Foes -- 23. Toxic Plants and Phytochemicals -- Chukwuebuka Egbuna et al. -- 24. Phytochemicals as Prooxidants -- Andrew G. Mtewa -- 25. Phytochemical as an Antinutrient -- Chukwuebuka Egbuna.
Includes bibliographical references and index.
Also available in print format.
Keywords: MEDICAL / Alternative Medicine; MEDICAL / Pharmacology; Phytochemicals; Drugs -- Research; Electronic books